1994
DOI: 10.1152/ajpheart.1994.266.4.h1565
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate and heart rate variability as indexes of sympathovagal balance

Abstract: According to the Rosenblueth-Simeone model, the heart rate (HR) is proportional to the sympathovagal balance. The individual proportionality constant is the intrinsic heart rate, which can only be determined invasively. The normalized low-frequency heart rate variability power (LF) has been raised as a calibrated noninvasive alternative. To concrete this assumption, we studied the individual LF-HR relation during incremental head-up tilt (0, 10, 20, 30, 40, 45, 50, 55, 60, 65, 70, 75, and 80 degrees) in 21 you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(107 citation statements)
references
References 0 publications
6
98
0
3
Order By: Relevance
“…In large epidemiological studies as ours, it is often not feasible to invasively or pharmacologically measure sympathetic activity and we therefore used surrogate markers of sympathetic activation. However, HR and HR variability are wellestablished parameters of autonomic function (15,16). HR is influenced by sympathetic and parasympathetic outflow to the sinus node, and dominant sympathetic activation over parasympathetic activation results in a higher HR and less variability in HR.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…In large epidemiological studies as ours, it is often not feasible to invasively or pharmacologically measure sympathetic activity and we therefore used surrogate markers of sympathetic activation. However, HR and HR variability are wellestablished parameters of autonomic function (15,16). HR is influenced by sympathetic and parasympathetic outflow to the sinus node, and dominant sympathetic activation over parasympathetic activation results in a higher HR and less variability in HR.…”
Section: Tablementioning
confidence: 99%
“…Electrocardiographic markers that are commonly used to study sympathetic activation are heart rate (HR) and HR variability (15,16). Three recent experimental studies showed that the sympathetic overdrive is also reflected in other changes on the standard electrocardiogram (ECG) (17).…”
Section: Introductionmentioning
confidence: 99%
“…Resultados [1][2][3][4] . Estudos recentes 5-8 têm demonstrado que a diminuição da VFC está relacionada a um maior índice de morbidade e mortalidade cardiovascular.…”
Section: Métodos -Dezessete Homens (28±6 Anos) Realizaram Teste Ergoeunclassified
“…Nineteen of the respondents refused to carry a Holter recorder. Seventeen shift workers refused to finish the first measurement or to enrol for the second measurement because "it was to cumbersome" (10) or due to due to skin irritation (7). Seven recordings could not be used due to a poor signal to noise ratio (4) or technical malfunction of the equipment (3).…”
mentioning
confidence: 99%